Screening of Hibiscus and Cinnamomum Plants and Identification of Major Phytometabolites in Potential Plant Extracts Responsible for Apoptosis Induction in Skin Melanoma and Lung Adenocarcinoma Cells - Kaushik, Neha; Oh, Hyunji; Lim, Yeasol; Kumar Kaushik, Nagendra; Nguyen, Linh Nhat; Choi, Eun Ha; Kim, June Hyun (Frontiers in Bioengineering and Biotechnology, 2021)
Carcinogenesis is a major concern that severely affects the human population. Owing to persistent demand for novel therapies to treat and prohibit this lethal disease, research interest among scientists is drawing its huge focus towards natural products since they have minimum toxicity comparable to existing treatment methods. The plants produce secondary metabolites which are known to have the anti-cancer potential for clinical drug development. Furthermore, the use of nanocarriers could boost the solubility and stability of phytocompounds, to obtain site-targeting delivery. The identification of potential phytochemicals in natural compounds would be beneficial for the synthesis of biocompatible nanoemulsions. The present study aimed to investigate the potential cytotoxicity of ethanol extracts of Hibiscus syriacus and Cinnamomum loureirii Nees plant parts on human skin melanoma (G361) and lung adenocarcinoma (A549) cells. Importantly, biochemical analysis results showed the presence of high phenol (50-55µgGAE/mg) and flavonoids (42-45µgQE/mg) contents with good antioxidant activity (40-58 %) in Cinnamomum loureirii Nees plants extracts. This plant possesses potent anti-proliferative activity (60 - 90%) on the malignant G361 and A549 and cell lines which are correlated with the production of nitric oxide. Especially, Cinnamomum loureirii plant extracts have major metabolites which exhibit cancer cell death associated with cell cycle arrest. These findings support the potential application of Cinnamomum for the development of therapeutic nanoemulsion in future cancer therapy.